Evolusi Kajian Manajemen Pendidikan, Kinerja Guru, dan Evaluasi Kurikulum di Indonesia: Tinjauan Literatur Sistematis - Sertin Allolayuk; Fries Sigilipu; Yosafat Tabasi; Irsan Tondowala; Sulvia Tondowala; Yuyun Tobondo; Masril Tudjuka; Elisabet Djunaidy; Yunda Tobondo; Novalinda Mohamad; Agustanty Ruagadi; Yohanis Tarukallo; I Ketut Yakobus (Journal on Education, 2025)
This study aims to map the development, thematic patterns, and conceptual relationships in research on education management, teacher performance, and curriculum evaluation in Indonesia using a systematic literature review approach. The study applied a PRISMA-based design to select relevant open-access journal articles from the Scopus database, resulting in twelve studies included for analysis. Data were analyzed through thematic and relational synthesis to identify topic distribution, inter-variable relationships, and research trajectories. The results show that Indonesian education literature concentrates on educational governance, teacher professionalism, and data-driven curriculum evaluation across contexts such as Islamic education, the Merdeka Curriculum, inclusive education, and disaster risk reduction. The most consistent relationship forms a systemic chain between management, curriculum evaluation, and teacher performance. Furthermore, the evolution of research indicates a shift from normative approaches toward performance-oriented, accountable, and evidence-based educational governance. The study concludes that education research in Indonesia, within the analyzed corpus, is moving toward a paradigm of education as a managed and continuously evaluated system, providing a structured map of research trends to support future studies and policy development.